Impact of carbon emission difference on the dual-channel fresh produce supply chain with capital constraints - Bai, Shizhen; Jia, Xuelian (Frontiers in Environmental Science, 2023)
The dual-channel marketing mode of online and offline integration plays an important role in promoting the development of the agricultural economy. However, few studies involve the optimal operation decision and financing mode selection strategy of the dual channel supply chain of fresh agricultural products when suppliers are constrained by capital, especially when considering the difference in carbon emissions. We build a Stackelberg game model of a dual-channel supply chain under the financing strategy of banks and retailers to study the optimal operation decision and financing strategy selection. Our analysis results show that the supplier always chooses the retailer financing strategy when the retailer's interest rate and carbon emission difference are within certain thresholds. In addition, we find that suppliers' financing behavior, carbon emission differences, and consumers' environmental awareness have a significant impact on suppliers' and retailers' decision-making. Our work provides long-term sustainable financing strategies and management insights for enterprises in the dual-channel fresh produce supply chain in the context of a low-carbon economic environment and promotes the stable development of the agricultural economy.